TREND ANALYSIS OF PROPORTIONAL MORTALITY FROM CARDIOVASCULAR DISEASE MACAÉ, 1996-2011 (Fiep Bulletin - online, 2016)
In Brazil, cardiovascular diseases (CVD) are still one of today's most important health problems, corresponding to the first cause of death in all regions of the country, in both sexes. This study aimed to analyze the trend of proportional mortality from CVD in the city of Macaé, between 1996 and 2011. We conducted a study of time series on proportional mortality from CVD in the period 1996-2011. Secondary data on deaths by residence, by ICD-10 Chapter, were collected from the MS/SVS/DASIS – Mortality Information System – SIM/Macaé. We conducted the linear trend analysis of proportional mortality from CVD. It turned out that in 1996, the proportional mortality from CVD was 32.38; in 1997 it was 26.61; in 1998 it was 30.35; in 1999 it was 34.30; in 2000 it was 31.38; in 2001 it was 30.5; in 2002 it was 30.77; in 2003 it was 29.17; in 2004 it was 27.87; in 2005 it was 28.44; in 2006 it was 27.13; in 2007 it was 25.87; in 2008 it was 24.73; in 2009 it was 29.61; in 2010 it was 27.0; in 2011 it was 26.47. We conclude that there is a downward trend in proportional mortality from CVD, but is still representing the leading cause of death in the city of Macaé, Rio de Janeiro.
Keywords: Diseases of the Circulatory System; Mortality Ratio; Public Health.